Analysis of the Quality of Pharmaceutical Services at Outpatient Health Centers, East Sumba Regency, Indonesia - Talalab, Silvia Claudia; Jason M. Peranginnangin; Tri Wijayanti (HM Publisher, 2024)
Public administration services are one way to demonstrate maximum government performance in providing welfare and meeting community needs. One important sector in public services is pharmaceutical services at Health Centers. This research uses a descriptive method with a cross-sectional design. Primary data was obtained through observation, interviews and documentation. Secondary data was obtained from the 2022 Health Centers Medicine Usage Report and Request Sheet (LPLPO) and the 2021 Health Centers Drug Requirements Plan (RKO). Of the 28 indicators of the quality of pharmaceutical services, 15 of the third indicators of the Health Centers meet the standards, 10 of the third indicators of the Health Centers do not meet the standards, 1 indicators only one Health Center meets and 2 indicators only two Health Centers fulfill. Factors that influence the quality of management of pharmaceutical preparations at the East Sumba Regency outpatient Health Centers are human resources that do not come from pharmacy. The quality of pharmaceutical services at the East Sumba Regency outpatient Health Centers still needs to be improved. Pharmacists are needed as pharmaceutical personnel to maximize pharmaceutical services to the community.